Theoretical calculation of oxygen equilibrium isotope fractionation factors involving various NOy molecules, OH, and H2O and its implications for isotope variations in atmospheric nitrate. (15th October 2016) - Walters, Wendell W.; Michalski, Greg
Abstract: The oxygen stable isotope composition (δ 18 O) of nitrogen oxides [NO x = nitric oxide (NO) + nitrogen dioxide (NO2 )] and their oxidation products (NO y = NO x + nitric acid (HNO3 ) + particulate nitrate (p-NO3 − ) + nitrate radical (NO3 ) + dinitrogen pentoxide (N2 O5 ) + nitrous acid (HONO) + …) have been shown to be a useful tool for inferring the proportion of NO x that is oxidized by ozone (O3 ). However, isotopic fractionation processes may have an influence on δ 18 O of various NO y molecules and other atmospheric O-bearing molecules pertinent to NO x oxidation chemistry. Here we have evaluated the impacts of O isotopic exchange involving NO y molecules, the hydroxyl radical ( OH), and water (H2 O) using reduced partition function ratios ( x β) calculated by hybrid density functional theory. Assuming atmospheric isotopic equilibrium is achieved between NO and NO2 during the daytime, and NO2, NO3, and N2 O5 during the nighttime, δ 18 O–δ 15 N compositions were predicted for the major atmospheric nitrate formation pathways using our calculated exchange fractionation factors and isotopic mass-balance. Our equilibrium model predicts that various atmospheric nitrate formation pathways, including NO2 + OH → HNO3, N2 O5 + H2 O + surface → 2HNO3, and NO3 + R → HNO3 + R will yield distinctive δ 18 O–δ 15 N compositions. Our calculated δ 18 O–δ 15 N compositions match well with previous atmospheric nitrate measurements, and will potentially help better understand the role oxidation chemistry plays on the N and O isotopic composition of atmospheric nitrate.